SIFAT VENIR DAN KAYU LAPIS ENAM JENIS KAYU UNTUK HUTAN TANAMAN INDUSTRI - Rodjak Memed; M I Iskandar; Paribotro Sutigno (Jurnal Penelitian Hasil Hutan, 1990)
The characteristics studied are peeling  properties, physical properties of  the  veneer,  gluing  properties  and  some physical   and  mechanical  properties of  the  plywood  (both   triplex and  multiplex).All logs from 6 wood species could be peeled satisfactorily in cold condition. Veneer  of  1.5 mm  thickness could be produced at cutting angle  between  90° 30’- 92°.Average shrinkage of  the  veneer is 6.52% and  average veneer  swelling  from  oven  dry to air dry condition is 4.11%. Water resistant bonding  strength for all wood species  studied meet  Indonesian, Japanese and German  standard. Average thichness  reduction  due to pressing in the plywood  manufacturing  process  is 0.31mm.  The mechanical  properties of plywood vary among  the wood  species.